2012
DOI: 10.3346/jkms.2012.27.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postnatal Dexamethasone or Hydrocortisone in a Rat Model of Antenatal Lipopolysaccharide and Neonatal Hyperoxia Exposure

Abstract: The aim of our study was to investigate the differential effects of dexamethasone (DXM) and hydrocortisone (HCS) on somatic growth and postnatal lung development in a rat model of bronchopulmonary dysplasia (BPD). A rat model of BPD was induced by administering intra-amniotic lipopolysaccharide (LPS) and postnatal hyperoxia. The rats were treated with a 6-day (D1-D6) tapering course of DXM (starting dose 0.5 mg/kg/day), HCS (starting dose 2 mg/kg/day), or an equivalent volume of normal saline. DXM treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…To evaluate the effects of oxygen and HC exposure on alveolar growth, mean alveolar area and mean chord length were measured in hematoxylin-stained lung sections. Similar to previous reports ( 10 , 22 ), hyperoxia exposure increased both mean alveolar area and mean chord length (137±3% and 128±4% respectively vs. normoxia-vehicle) ( Figure 3 ). Alveolar simplification was worsened in hyperoxic animals treated with 10 mg/kg HC but was not significantly affected by lower HC doses ( Figures 3 and 4 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To evaluate the effects of oxygen and HC exposure on alveolar growth, mean alveolar area and mean chord length were measured in hematoxylin-stained lung sections. Similar to previous reports ( 10 , 22 ), hyperoxia exposure increased both mean alveolar area and mean chord length (137±3% and 128±4% respectively vs. normoxia-vehicle) ( Figure 3 ). Alveolar simplification was worsened in hyperoxic animals treated with 10 mg/kg HC but was not significantly affected by lower HC doses ( Figures 3 and 4 ).…”
Section: Resultssupporting
confidence: 91%
“…This was evidenced in our model as demonstrated by increased mean alveolar area and chord length in animals exposed to chronic hyperoxia ( Figure 3 ) ( 24 ). Glucocorticoids alone have been known to adversely affect alveolar growth, with HC being reported as less detrimental compared to dexamethasone ( 22 , 32 ). In our study, we observed dose-dependent effects of HC on alveolar growth with worsening alveolar simplification associated with increasing HC doses during hyperoxia exposure ( Figures 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, intra-amniotic LPS and subsequent postnatal hyperoxia caused an arrest in alveolar and pulmonary vascular development, which is the hallmark of BPD, in a newborn rat model 10,11,13,14. In the present study, the RGZ treatment was found to preserve alveolar and pulmonary vascular development against the detrimental influence of intra-amniotic inflammation and postnatal hyperoxia.…”
Section: Discussionsupporting
confidence: 62%
“…The newborn rat pups which were exposed to intra-amniotic LPS were then exposed to 80% O 2 in a Plexiglas chamber with adaptors to supply and vent gas (BPD groups), and pups which were exposed to vehicle were kept in room air (No BPD groups) with their dams for 7 days beginning on the day of birth (P1), as previously described. 10 To the newborn rat pups in the BPD groups, 80% O 2 was constantly administered using mass flow controllers (TSC-220; MFC Korea, Suwon, Korea). Nursing rat dams were switched between 80% O 2 and air every 24 hour to avoid oxygen toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal resuscitation of premature infants between 24 and 26 weeks (canalicular stage) with 30% O2 instead of 90% O2 decreases the incidence of BDP at 36 weeks by a factor of about 2 (46). In a newborn rat model of BPD induced by intra-amniotic LPS administration and postnatal hyperoxia, there is an arrest in alveolar and pulmonary vascular development, which is a hallmark of BPD (4750). Hyperoxia-induced neonatal lung injury is associated with activation of Wnt/β-catenin signaling and inhibition of WNT/β-catenin signaling attenuates hyperoxia-induced pulmonary hypertension in neonatal rats (51, 52).…”
Section: Introductionmentioning
confidence: 99%